Clinical efficient risks, associated with clinic-epidemiological and clinic-nosological risk-creating factors in thoraco-cranial trauma - S. O. Gurev; V. V. Khmel (Клінічна хірургія)
Objective. Formulation of clinical efficient risks, associated with- clinic-epidemiological signs and clinic-nosological forms of injuries.